Hipertensi dan Faktor Risikonya di Puskesmas Motolohu Kabupaten Pohuwato - Arda, Zul Adhayani; Ali, Rifa’i; Mustapa, Marselina (Gorontalo Journal of Public Health, 2018)
Based on WHO (World Health Organization) in 2011, hypertension was causing 8billion of the world citizen pass away every year in which almost 1.5 billion of them were in south east of Asia. The purpose of study was to determine the risk factors associated with hypertension in Pohuwato District in 2017. The study was an observational analytic with case control design. The sample of study was 202 respondents which divided into 101 case group and 101 control group in the  w orkarea of Puskesmas Motolohu in Pohuwato District. The data were analyzed by using odds ratio (OR) test. The study result showed that occupation (OR=2.71;95% CI; 1.45-5.05), gender (OR=2.55; 95% CI; 1.35-4.79), smoking behavior (OR=2.55; 95% CI; 1.35-4.79), hypertension history (OR=6.13; 95% CI; 3.04-12.36), and consumption of coffee (OR=3.20; 95% CI; 1.64-6.25) were significant risk factors for occurance of hypertension. It is recomended to counseled as a means of disseminating information about risk factors and effect of hypertensionto the public.